Whither Anthropology without Nation-state? Interdisciplinarity, World Anthropologies and Commoditization of Knowledge - Pobłocki, Kacper (SAGE, 2009)
Debates on `native anthropology', `anthropologies of the South', `peripheral anthropologies' and so forth have usually focused on colonialism as the main culprit of asymmetric relations between anthropological knowledges. By bringing the recent dispute between Western and `native' anthropologists of post-socialism into the `world anthropologies' debate, I seek to highlight those aspects of current epistemic inequalities that are not postcolonial in nature, but result from global commoditization of knowledge. I ponder why Western anthropologists who started visiting Eastern Europe from the 1970s, concluded that `native' academic knowledge is inferior to their own output. This was not due to a prejudice brought from afar, I argue, but rather was a result of their field experiences. I discuss how three types of native `captive minds' (communist, nationalist and neoliberal) emerged, and how encountering (or learning about) them made Western anthropologists uninterested in (and distrustful of) local epistemic production. I focus on the putative nationalist `captive mind', and argue that the straw man of East European `positivist' science (as opposed to the superior `theory-oriented' Western anthropology) emerged due to recent changes in the political economy of the academia. I show how the `theoretical turn' was experienced differently in Western and Polish academia, and how these changes, explained by the different regimes of value, show that there has been an increase only in `ritual' exchange between parochial and metropolitan anthropology rather than meaningful communication.
Keywords: commoditization of knowledge; historical anthropology; post-colonialism; post-socialism; world anthropologies; world-systems analysis